Pañcāyat e vyavahāra: una prospettiva sulle dinamiche locali di dispute settlement in India - Correndo, Chiara (Comporre il conflitto, 2020)
The contribution aims at discussing the concept of mediation within the framework of Hindu local communities. After introducing the theoretical debate related to the concept of vyavahāra, the contribution will focus on the pañcāyat, the local assembly. It will be analyzed as both a dispute settlement forum and an intermediate level group, following the lines of Davis, which plays a key role in the bilateral flux of norms between the local and the institutional level and in the consequent vivification of Hindu law.